A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

A qualitative peptide biomarker approach to identify piscine gelatine in products to support food security - Helen H. Grundy; Carla Soto Quintana; Kristine Korzow Richter; Wendy A. Read; Matthew L. Hutchinson; Antony Stephen Lloyd; James Anthony Donarski (Food Additives & Contaminants: Part A, 2023)

Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic - Paul W. Hill; Richard Broughton; Jeremy Bougoure; William Havelange; Kevin K. Newsham; Helen Grant; Daniel V. Murphy; Peta Clode; Soshila Ramayah; Karina A. Marsden; Richard S. Quilliam; Paula Roberts; et al. (Ecology Letters, 2019)
In contrast to the situation in plants inhabiting most of the world’s ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO 2 .

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Long-term biomonitoring of lichen and bryophyte biodiversity at Burnham Beeches SAC and global environmental change - O. William Purvis; I. Tittley; P. D. Jim Chimonides; Roger Bamber; Peta A. Hayes; Peter W. James; Fred J. Rumsey; Helen Read (Systematics and Biodiversity, 2010)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Invertebrates in Woodlands Polluted by Heavy Metals – – An Evaluation Using Canonical Correspondence Analysis - Helen J. Read; M. H. Martin; J. M. V. Rayner (Water, Air, & Soil Pollution, 1998)